Sexual dimorphism in relationships between of plasma urea and some psycho-neuro-endocrine parameters - Bombushkar, Igor; Anchev, Anatoliy; Żukow, Xawery; Popovych, Igor (Journal of Education, Health and Sport, 2022)
Background. Earlier we found a strong urato-neural relationships in both men and women. Moreover, in women, the factor structure of the neural root is almost completely different from that in men. In addition, significant differences were found between the profiles of urato-neural correlations of women of reproductive age and postmenopausal women. The purpose of this study is to analyze the relationships between the plasma urea level and some psycho-neuro-endocrine parameters in the same cohort. Materials and Methods. The object of observation were almost healthy volunteers: 31 males (24÷69 y) and 30 females, from among them 18 postmenopausal (48÷76 y) and 12 of reproductive age (30÷45 y). In basal conditions we determined plasma levels of urea and adaptation hormones, estimated the severity of the trait and reactive anxiety, recorded the ongoing HRV and EEG. After 4 or 7 days, repeated testing was performed. Results. By building regression models with stepwise exclusion, it was found that in men plasma urea positively determines (R2=0,499) the level of circulating catecholamines and power spectrum density (PSD) of δ-, θ- and β-rhythms in different loci. In postmenopausal women, urea downregulates the amplitude and PSD of δ-rhythm in different loci, instead, it upregulates the PSD of α-rhythm in T5 locus, entropy of EEG in 2 loci and vagal tone. The degree of determination of neural parameters is 71,6%. In women of reproductive age the degree of determination of neural parameters is similar (69,9%), but the factor structure of the model is completely different. Urea upregulates the PSD of β-rhythm in F7 locus while downregulates the levels of reactive anxiety, vagal tone, entropy of EEG in 3 loci and P4-θ PSD as well as causes left lateralization of θ- and α-rhythms. Conclusion. Plasma urea has a modulating effect on EEG&HRV parameters, as well as reactive anxiety, but this effect is significantly different in men and women of different ages.